'In trust for the three nations'? The India Office Library & Records dispute, 1947–72. Issue 2 (3rd April 2023) - Ankit, Rakesh
ABSTRACT: Between 1947 and 1972, governments of India and Pakistan laid claims to ownership, management and share of the India Office Library & Records. These attempts and the British government's responses to them have been bypassed by scholars of decolonisation. This article traces the trajectory of that dispute's three distinct phases, wherein different proposals were mooted to wrest and retain, respectively the riches and records of the IOL&R. Unlike the more-studied African and Southeast Asian cases from the former British Empire, this dispute was less clear-cut and therefore more demanding of both sides in their manoeuvres to pursue their desires. Legal, administrative and technical bids were made in historical and moral arguments, with cultural and economic factors listed in support. In providing their details, this article demonstrates a difficult episode for decolonisation, where at stake was both its curated imperial past and yet-to-be written national narratives. It shows how symbols of a shared history as well as sources of that history's separate writing became an arena of contest as much for the old glory as for new profits. At a time when decolonising history is in vogue, this article depicts the difficulties of even diversifying the artefacts of colonial history.